La médiation de textes en tant que compétence. Le cas des étudiants se présentant à l’examen de certification en langue étrangère à l’Université de Varsovie - Kucharczyk, Radosław (Neofilolog, 2023)
The purpose of this article is to present the results of empirical research conducted with students taking a foreign language certification test. The aim of the study was to diagnose the extent to which the students interviewed are able to mediate texts. In other words, we wanted to examine whether they possess the knowledge and skills necessary to reconstruct the meanings of a text in order to convey the information imposed by the examination task. The article begins with a short presentation of the notion of mediation. It then discusses the place it has been given in the language classroom by the designers of the CEFR. Finally, we present our empirical study: we define its theoretical framework, present the survey questionnaire we used and then proceed to the analysis of the data collected and the discussion of the results.